STRATEGI KOMUNIKASI PENINGKATAN ENGAGEMENT (LIKE, SHARE, DAN COMMENT) TIKTOK @UNIVERSITAS DIPONEGORO DAN INSTAGRAM @UNDIP.OFFICIAL MELALUI PRODUKSI KONTEN VIDEO SEBAGAI PROJECT COORDINATOR DAN CONTENT PLANNER - Estya Rastra Pratidina; Joyo Nur Suryanto Gono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
(UNDIP) has proactively adopted digital communication channels as a strategicinstrument to strengthen its institutional reputation. As a higher education institution targetingGeneration Z, UNDIP faces challenges in building effective interaction on social media,particularly on the TikTok platform. Content that tends to be formal and one-way is often lesseffective in attracting young audiences who prefer a humanistic, inclusive, and interactivenarrative approach. This professional project aims to design and implement a communicationstrategy through the